2023
DOI: 10.5935/0004-2749.20230062
|View full text |Cite
|
Sign up to set email alerts
|

The importance of considering the possibility of ocular sporotrichosis in areas with high incidence rates of sporotrichosis

Abstract: Ocular sporotrichosis involving adnexa can present in 4 types: granulomatous conjunctivitis, dacryocystitis, Parinaud oculoglandular syndrome, and bulbar conjunctivitis. The incidence of ocular sporotrichosis has increased in regions with high incidence rates of sporotrichosis. We present a series of three cases of ocular involvement by the fungus Sporothrix species, including its manifestations, approaches, and relevance in areas where sporotrichosis has considerable incidence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Ocular sporotrichosis occurs mainly because of direct contact of the ocular mucosa of a person with secretions from an infected cat, usually because of cutaneous exudates or respiratory droplets expelled during cat sneezing (5,12,26). Ocular sporotrichosis is characterized by acute or chronic conjunctivitis, including Parinaud ocular syndrome and dacryocystitis (2,12,(38)(39)(40)(41). We also observed that unusual clinical manifestations of CTS increased from 2018 onward, coinciding with the epidemic increase in the number of cases of the disease.…”
Section: Discussionmentioning
confidence: 64%
“…Ocular sporotrichosis occurs mainly because of direct contact of the ocular mucosa of a person with secretions from an infected cat, usually because of cutaneous exudates or respiratory droplets expelled during cat sneezing (5,12,26). Ocular sporotrichosis is characterized by acute or chronic conjunctivitis, including Parinaud ocular syndrome and dacryocystitis (2,12,(38)(39)(40)(41). We also observed that unusual clinical manifestations of CTS increased from 2018 onward, coinciding with the epidemic increase in the number of cases of the disease.…”
Section: Discussionmentioning
confidence: 64%